1985
DOI: 10.1210/endo-117-2-711
|View full text |Cite
|
Sign up to set email alerts
|

In VivoGonadotropin-Releasing Hormone Release and Serum Luteinizing Hormone Measurements in Ovariectomized, Estrogen-Treated Rhesus Macaques*

Abstract: The push-pull perfusion technique was used to measure GnRH release in unanesthetized female rhesus macaques (Macaca mulatta) and to examine the dynamic relationship between GnRH release and LH levels during the estrogen-induced LH surge. Each ovariectomized macaque was anesthetized and stereotaxically fitted with a push-pull cannula directed into the median eminence (ME). After at least 1 week of recovery, each animal received an estradiol benzoate (E2B) injection (42 micrograms/kg BW) or an oil (OIL) injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(92 citation statements)
references
References 37 publications
6
86
0
Order By: Relevance
“…In particular, the present results are consistent with observations in the spontaneously cycling cow, sheep, and human, i.e., estimated LH pulse frequency increases in the late follicular phase as circulating concentrations of estrogenic and other hormones rise before the LH surge (12,33,34). Moreover, in the estrogen-treated ovariectomized rhesus monkey, a burstlike increase in endogenous GnRH neurosecretion occurs in conjunction with the induced LH surge (35). These experimental findings are consistent with our observations on days 5 and 10 ofaugmented LH pulse frequency in the estrogen-replaced postmenopausal setting.…”
Section: Resultssupporting
confidence: 92%
“…In particular, the present results are consistent with observations in the spontaneously cycling cow, sheep, and human, i.e., estimated LH pulse frequency increases in the late follicular phase as circulating concentrations of estrogenic and other hormones rise before the LH surge (12,33,34). Moreover, in the estrogen-treated ovariectomized rhesus monkey, a burstlike increase in endogenous GnRH neurosecretion occurs in conjunction with the induced LH surge (35). These experimental findings are consistent with our observations on days 5 and 10 ofaugmented LH pulse frequency in the estrogen-replaced postmenopausal setting.…”
Section: Resultssupporting
confidence: 92%
“…However, the pulsatile pattern of GnRH neurosecretion can not be detected in peripheral blood because of a rapid turnover and dilution of GnRH in the peripheral circulation. The temporal relationship between GnRH pulses and LH pulses has been documented so far in the monkey [15,16], sheep [2][3][4]17], rabbit [18], rat [19,20] and horse [21]. In the present study, we adapted the portal blood sampling technique, which had been originally developed for sheep, for use in goats and confirmed that GnRH pulses were associated with LH pulses in all the ovariectomized goats examined.…”
Section: Discussionsupporting
confidence: 78%
“…The GnRH pulses in the perfusate were characterized by their rather blunt pattern of increase, which was similar to those obtained by the pushpull method [4][5][6][7] but in contrast to sharp pulses observed in sequentially collected pituitary portal blood [1-3, 17, 18]. This may arise from the similarity between the principles of the microdialysis and push-pull methods, since both methods provide information on the extracellular GnRH concentration as a summation in a given time.…”
Section: Discussionsupporting
confidence: 53%
“…In vivo GnRH secretion has been examined by either pituitary portal blood sampling [1][2][3] or the push-pull cannulae method [4][5][6][7]. However, these methods have practical disadvantages arising mainly from technical difficulties which have hindered them from being widely adopted.…”
Section: Introductionmentioning
confidence: 99%